2016
DOI: 10.1051/0004-6361/201526958
|View full text |Cite
|
Sign up to set email alerts
|

Mg line formation in late-type stellar atmospheres

Abstract: Context. Mg is the α element of choice for Galactic population and chemical evolution studies because it is easily detectable in all late-type stars. Such studies require precise elemental abundances, and thus departures from local thermodynamic equilibrium (LTE) need to be accounted for. Aims. Our goal is to provide reliable departure coefficients and equivalent widths in non-LTE, and for reference in LTE, for diagnostic lines of Mg studied in late-type stars. These can be used, for example, to correct LTE sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Here, we focus on the NLTE abundance corrections in our program stars, and explore the sensitivity of NLTE corrections to model atmosphere structure. Table 3 compares our NLTE corrections for selected models with the NLTE corrections determined by Osorio & Barklem (2016). The agreement is good.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Here, we focus on the NLTE abundance corrections in our program stars, and explore the sensitivity of NLTE corrections to model atmosphere structure. Table 3 compares our NLTE corrections for selected models with the NLTE corrections determined by Osorio & Barklem (2016). The agreement is good.…”
Section: Resultsmentioning
confidence: 75%
“…We can test the corresponding errors in ∆A(Mg) by assuming that the uncertainty of the T (τ ) relationship can be approximated by a systematic shift in T eff . This is, of course, not a fully correct assumption, because also the Osorio & Barklem (2016). The data were computed using 1D hydrostatic model atmospheres, MAFAGS-OS in this work and MARCS in Osorio & Barklem (2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhances the role that inelastic hydrogen collision rates can play for a NLTE abundance determination. Recently, it has been shown that the chargetransfer (i.e., ion-pair production 4 ) processes can domi-nate over excitation processes (Osorio et al 2015;Osorio & Barklem 2016;Ezzeddine et al 2016b). Cross-section calculations for Li+H and Na+H (Barklem et al 2010), for example, have shown that the largest cross sections for excitation are small compared with those for ion-pair production from certain energy states.…”
Section: Iron Model Atommentioning
confidence: 99%
“…There are several studies on NLTE analysis of neutral magnesium including the recent studies of Bergemann et al (2015), Osorio & Barklem (2016). The former studied NLTE effects in the J-band Mg i lines and, due to a lack of experimental log(g f ) values, calculated log(g f ) values were used.…”
Section: Introductionmentioning
confidence: 99%